Mechanism of tonifying-kidney Chinese herbal medicine in the treatment of chronic heart failure - Chen, Lizhen; Yu, Dayun; Ling, Shuang; Xu, Jin-Wen (Frontiers in Cardiovascular Medicine, 2022)
According to traditional Chinese medicine (TCM), chronic heart failure has the basic pathological characteristics of “heart-kidney yang deficiency.” Chronic heart failure with heart- and kidney-Yang deficiency has good overlap with New York Heart Association (NYHA) classes III and IV. Traditional Chinese medicine classical prescriptions for the treatment of chronic heart failure often take “warming and tonifying kidney-Yang” as the core, supplemented by herbal compositions with functions of “promoting blood circulation and dispersing blood stasis.” Nowadays, there are still many classical and folk prescriptions for chronic heart failure treatment, such as Zhenwu decoction, Bushen Huoxue decoction, Shenfu decoction, Sini decoction, as well as Qili Qiangxin capsule. This review focuses on classical formulations and their active constituents that play a key role in preventing chronic heart failure by suppressing inflammation and modulating immune and neurohumoral factors. In addition, given that mitochondrial metabolic reprogramming has intimate relation with inflammation, cardiac hypertrophy, and fibrosis, the regulatory role of classical prescriptions and their active components in metabolic reprogramming, including glycolysis and lipid β-oxidation, is also presented. Although the exact mechanism is unknown, the classical TCM prescriptions still have good clinical effects in treating chronic heart failure. This review will provide a modern pharmacological explanation for its mechanism and offer evidence for clinical medication by combining TCM syndrome differentiation with chronic heart failure clinical stages.